A Model of Speaking Teaching Materials for Primary English Teachers’ Candidates Based On Contextual Approach - Dayu Retno Puspita; Asih Rosnaningsih (Universitas Lancang Kuning, 2020)
The purpose of this research is to develop teaching materials in English speaking skills that are suitable for the needs of primary English teachers’ candidates in the Teacher Training and Education Faculty of Muhammadiyah University of Tangerang. The research is designed with a research and development study or R and D cycle consisting of seven steps: literature study, needs analysis, syllabus analysis, teaching material development, product validation, product testing and final product. Data collection techniques used observation, interview, questionnaire and product tests. The findings of the study reveal that 12 chapters of speaking teaching material was chosen for Primary English teachers’ candidates based on contextual approach, namely: greeting and introducing, counting numbers, talking about family, describing objects, talking about houses, school and class environment, telling time and talking about daily activity, talking about feeling and health issues, shopping time, asking and giving directions, talking about plans and telling past experiences. The results of the effectiveness test show that speaking teaching materials are stated to be good. These findings call for lecturers to apply the teaching material developed in the learning process as a main reference or as a supplementary material so that it can make learning material more interesting, innovative, and effective.